Up and running with AutoCAD 2012 : 2D and 3D drawing and modeling - Gindis, Elliot (Waltham, MA : Academic Press, 2012)
"Throughout the book, the following methods are used to present material: - Explain the new concept or command and why it is important. - Cover the command step by step (if needed), with your input and AutoCAD responses shown so you can follow and learn them. - Give you a chance to apply just-learned knowledge to a real-life exercise, drawing, or model. - Test yourself with end-of-chapter quizzes and drawing exercises that ask questions about the essential knowledge"--Provided by publisher.
Includes index.
Machine generated contents note: Part One Beginner to Intermediate Chapter One AutoCAD Fundamentals 1 Chapter Two AutoCAD Fundamentals 2 Chapter Three Layers, Colors, Linetypes and Properties Chapter Four DText, MText, Style and Editing Chapter Five Bhatch Chapter Six Dimensions Chapter Seven Blocks and Wblocks Chapter Eight Polar and Rectangular Arrays, Polygon and Circle/TTR Chapter Nine Isometric Chapter Ten Basic Printing and Output Part II Intermediate to Advanced Chapter Eleven Advanced Linework Chapter Twelve Advanced Layers Chapter Thirteen Advanced Dimensions Chapter Fourteen Options, Shortcuts, CUI, Design Center & Exp. Tools Chapter Fifteen Miscellaneous Topics Chapter Sixteen Importing and Exporting Data Chapter Seventeen External References Chapter Eighteen Paper Space Chapter Nineteen Attributes Chapter Twenty Advanced Output and Pen Settings Part III 3D Chapter Twenty One 3D Basics Chapter Twenty Two Primitives Chapter Twenty Three Object Manipulation Chapter Twenty Four Boolean Operations Chapter Twenty Five Advanced 3D Tools I Chapter Twenty Six Advanced 3D Tools II Chapter Twenty Seven Meshes and Surfaces Chapter Twenty Eight UCS, Vports, Text and Dims in 3D Chapter Twenty Nine Cameras, Walk and Fly Chapter Thirty Lighting and Rendering Appendices.
Keywords: Computer graphics; Computer-aided design; Three-dimensional display systems